Nucleotide sequences of Bacillus subtilis flagellar biosynthetic genes fliP and fliQ and identification of a novel flagellar gene, fliZ. - Bischoff, D S (1992)
Three genes from the Bacillus subtilis major che-fla operon have been cloned and sequenced. Two of the genes encode proteins that are homologous to the Escherichia coli and Salmonella typhimurium flagellar biosynthetic proteins FliP and FliQ. The third gene, designated fliZ, encodes a 219-amino-acid protein with a predicted molecular mass of 24,872 Da. FliZ is not significantly homologous to any known proteins. Null mutants in fliP and fliZ do not have flagella; however, motility can be restored to the fliZ null mutant by expression of fliZ from a plasmid. FliZ has a conventional N-terminal signal sequence that does not direct secretion of the protein but appears to target the protein to the membrane. Two possible models of insertion of FliZ into the membrane are described.